Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Jasmani Dan Kesehatan Tentang Servis Atas Permainan Bola Volley Dengan Menggunakan Pendekatan Pembelajaran Driil Dan Bermain Di Kelas V SD Negeri 2 Ulim - Muhammad (Jurnal Kinerja Kependidikan (JKK): Facilities of Educator Career and Educational Scientific Information, 2023)
Improving Student Learning Outcomes in Physical and Health Education Subjects About Service for Volleyball Games Using a Drill and Play Learning Approach in Class V SD Negeri 2 Ulim. Based on the description of the background and scope above, the problems analyzed in this study are formulated as follows, Can the use of the drill and play learning approach improve student learning outcomes about the concept of serve for volleyball in class V SD Negeri 2 Ulim? drill and play can increase student learning activities about the concept of service for volleyball games in class V SD Negeri 2 Ulim Want to improve student learning outcomes by using a drill and play learning approach about the concept of service for volleyball games in class V SD Negeri 2 Ulim. Want to increase student learning activities about the concept of serving for volleyball in class V SD Negeri 2 Ulim, several conclusions can be drawn, namely that students’ attention will be emphasized on lessons if the teacher presents them using an appropriate approach can improve learning outcomes and student learning activities, this is evidenced from the average value of the formative test, for Physical Education subjects in class V, the pre-cycle score was 5.29, cycle 1 was 6.20 and cycle II was 8.1, it was seen that there was a significant increase from each cycle.